INFLUÊNCIA DO CONDICIONAMENTO MÁTRICO SOBRE A QUALIDADE FISIOLÓGICA DE SEMENTES DE ALGODÃO - VICENTE DE PAULA QUEIROGA; JOSÉ MARIA DURÁN; MARLEIDE MAGALHÃES DE ANDRADE LIMA; DIEGO ANTONIO NÓBREGA QUEIROGA; DYALLA RIBEIRO DE ARAUJO (Revista Caatinga, 2010)
The matriconditioning of seeds aims to improve the germination of seeds and to homogenize the establishment of seedlings in field. This study aimed to evaluate the physiological quality of cotton seeds immersed in solid matrix Algalita under different moisture and conditioning periods. We used seeds of cultivar Pantion cotton chemically delinted, coated in proportions of 100 g of seeds for 1000 g of Algalita. The treatments consisted of five levels of water used for wetting the matrix (10, 25, 50, 75 and 100 mL) during six conditioning periods (0, 1, 4, 8, 16 and 32 days). The experimental delineation was arranged as completely randomized, in the factorial project 5x6 (water texts x periods of conditioning) with four replications. The results indicate that there is a tendency to increase the vigor of seeds when they are stipulated in different levels of humidity in the solid matrix compared with the witness. This behavior happened exactly with the germination of the seeds, with the exception of the treatment of 1,00 mililiter of water.